2020
DOI: 10.1039/d0nr06270g
|View full text |Cite
|
Sign up to set email alerts
|

Pd nanoparticles as a plasmonic material: synthesis, optical properties and applications

Abstract: This review provides an overview of current progress into Pd nanoparticles supporting localized surface plasmon resonance and their applications. We begin by analyzing briefly the optical properties of Pd putting...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 128 publications
1
42
0
Order By: Relevance
“…Upon increasing light intensity (and so reaction temperature), the thermal contribution is more favored and clearly becomes predominant at temperatures above 200 °C. We hypothesize that the preeminent photo‐enhancement at temperatures below 200 °C derives mainly from the excitation of electron‐hole pairs in BTO together with the generation of hot electrons in Pd NPs [20] . These hot electrons arise from both LSPR and/or interband transitions in Pd NPs under UV and visible‐IR radiation [10b,d,e,21] …”
Section: Resultsmentioning
confidence: 99%
“…Upon increasing light intensity (and so reaction temperature), the thermal contribution is more favored and clearly becomes predominant at temperatures above 200 °C. We hypothesize that the preeminent photo‐enhancement at temperatures below 200 °C derives mainly from the excitation of electron‐hole pairs in BTO together with the generation of hot electrons in Pd NPs [20] . These hot electrons arise from both LSPR and/or interband transitions in Pd NPs under UV and visible‐IR radiation [10b,d,e,21] …”
Section: Resultsmentioning
confidence: 99%
“…Pd has been proven to be a good candidate because it supports good hydrogen absorption under normal temperature and pressure (Figure 4a), while still possessing considerable plasmonic properties. [95,96] Langhammer et al first used Pd nanodisks for direct LSPR sensors in 2007. [53] Pressure-LSPRresponse isotherms were observed and obeyed Sievert's law in the low-pressure range, exhibiting a characteristic "plateau" at 18 Torr upon hydrogen charging and 7.5 Torr upon hydrogen discharging.…”
Section: Direct Hydrogen Detection Based On Plasmonic Npsmentioning
confidence: 99%
“…2 For example, it has been previously demonstrated that the surface plasmon properties for Ag nanostructures can be tuned based on the void size, 2 making such nanostructures promising for a variety of applications including sensing, plasmon enhanced solar cells, Surface Enhanced Raman Spectroscopy (SERS) and photocatalysis. 2,41,42…”
Section: Materials Advancesmentioning
confidence: 99%
“…Furthermore, although only Cu hollow nanostructures were investigated for electrocatalysis in this work, hollow metal nanostructures including Ni, Ag, and Pd have many other potential applications, owing to their ability to generate surface plasmon resonance 2. For example, it has been previously demonstrated that the surface plasmon properties for Ag nanostructures can be tuned based on the void size, 2 making such nanostructures promising for a variety of applications including sensing, plasmon enhanced solar cells, Surface Enhanced Raman Spectroscopy (SERS) and photocatalysis 2,41,42. In summary, a templating technique for fabricating aligned and self-supporting arrays of hollow metal nanostructures was developed.…”
mentioning
confidence: 99%